Battery separator and process of preparation
Patent Information
- Application Number
- CN202610986585.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0048](1)解决界面分层与孔隙阻塞问题,提升电池能量密度:
Smart Images

Figure SMS_5 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery separator material technology, specifically to a battery separator and its preparation process. Background Technology
[0002] As a crucial component of lithium-ion batteries, the separator plays a vital role in electronic insulation and provides microporous channels to support ion migration between the positive and negative electrode materials. Its performance directly impacts the battery's capacity, cycle life, and safety. Polyolefin (PE and PP) microporous membranes are currently the most widely used commercial separators, characterized by low cost, excellent porosity, and good electrochemical stability. However, due to the low melting point of polyolefins (polyethylene 105-115℃, polypropylene 145-155℃), their non-polar surface, and limited mechanical properties, polyolefin separators exhibit poor thermal stability, electrolyte wettability, and resistance to lithium dendrite penetration, thus limiting their application in high-safety, high-energy-density batteries.
[0003] Currently, surface coating technology is the mainstream strategy for improving the performance of polyolefin separators. By introducing functional coatings with high thermal stability, excellent hydrophilicity, or high mechanical strength (such as inorganic ceramic particles like Al2O3, SiO2, ZrO2, and boehmite, or heat-resistant polymers like PVDF, aramid, and PI) onto the surface of the polyolefin separator, the overall performance of the separator can be significantly improved. However, surface coating technology often suffers from problems such as delamination due to insufficient adhesion between the coating and the substrate, decreased ionic conductivity due to excessive coating thickness blocking pores, and reduced energy density of lithium batteries due to increased separator weight, making it difficult to meet the stringent requirements of high-energy and high-power battery systems.
[0004] In addition, polyolefin materials are highly flammable. When a battery experiences thermal runaway or is short-circuited due to an external impact, the internal temperature of the battery will rise rapidly. The polyolefin separator will not only melt and shrink, but will also burn, becoming fuel for the fire and accelerating the spread of the fire, thus causing the battery to catch fire or even explode.
[0005] Therefore, this invention proposes a bulk modification strategy to prepare functionalized modified polyolefin resins through molecular structure design, and develop high-performance polyolefin membranes based on this, fundamentally solving the interfacial compatibility and pore blockage problems of surface coating technology, and achieving a synergistic improvement in membrane thermal stability, ionic conductivity and mechanical strength. Summary of the Invention
[0006] This invention provides a bulk-modified polypropylene composite masterbatch and its battery separator preparation process. On one hand, a hydrophilic polypropylene masterbatch is prepared by compounding plasticized modified polyvinyl alcohol resin with polypropylene resin under the action of a compatibilizer. On the other hand, a high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch is prepared by chemically bonding phosphate-modified nano-zirconia with heptavinyl POSS groups and DOPO-functionalized heptavinyl zirconium-containing POSS with polypropylene resin. The two masterbatches are then mixed with isotactic polypropylene resin, and a battery separator is prepared through a three-layer co-extrusion blow molding-stepwise biaxial stretching process. This separator product exhibits excellent heat resistance, hydrophilicity, ion conductivity, and mechanical strength, and achieves flame-retardant efficacy through a phosphorus-silicon-zirconia synergistic flame-retardant mechanism.
[0007] A battery separator, wherein the separator has a surface / intermediate / surface co-extruded structure;
[0008] The surface layer is formulated with 40-80 wt% isotactic polypropylene resin, 1-3 wt% nucleating agent, 0.5-2 wt% antioxidant and 17-57 wt% hydrophilic polypropylene masterbatch.
[0009] The intermediate layer is formulated with 40-80 wt% isotactic polypropylene resin, 1-3 wt% nucleating agent and 17-57 wt% high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch.
[0010] The hydrophilic polypropylene masterbatch is prepared by compounding plasticized modified polyvinyl alcohol resin with polypropylene resin under the action of a compatibilizer.
[0011] The high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch is prepared by compounding polypropylene resin with phosphate-modified nano-zirconia and DOPO-functionalized heptavinyl POSS groups via free radical grafting reaction and C-C covalent bonding.
[0012] Preferably, the phosphate-modified nano-zirconia carrying heptavinylPOSS groups is prepared by functionalizing heptavinylPOSS with diethyl phosphate and anchoring it to the surface of nano-zirconia via phosphate covalent bonds.
[0013] Preferably, the formulation of the hydrophilic polypropylene masterbatch is as follows:
[0014] 80-120 parts by weight of isotactic polypropylene resin;
[0015] 30-50 parts by weight of polyvinyl alcohol resin
[0016] 5-15 parts by weight of maleic anhydride-grafted polypropylene resin;
[0017] 3-8 parts by weight of glycerin.
[0018] Preferably, the formulation of the high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch is as follows:
[0019] 80-120 parts by weight of isotactic polypropylene resin;
[0020] 3-8 parts by weight of nano-zirconium dioxide;
[0021] 0.3-0.8 parts by weight of diethyl phosphate-functionalized heptavinyl POSS;
[0022] 1-5 parts by weight of DOPO functionalized heptavinyl zirconium-containing POSS;
[0023] 0.1-0.5 parts by weight of dicumyl peroxide;
[0024] 0.3-0.8 parts by weight of white oil.
[0025] Preferably, the particle size of the nano-zirconia is 20-30 nm.
[0026] Preferably, the nucleating agent is calcium pimecronate;
[0027] Preferably, the antioxidant is antioxidant 1010.
[0028] A process for preparing a battery separator includes the following steps:
[0029] Step 1: Using octavinyl-POSS as the starting material, diethyl phosphate-functionalized heptavinyl-POSS and DOPO-functionalized heptavinyl-zirconium-containing POSS were prepared respectively.
[0030] Step 2: The diethyl phosphate functionalized heptavinylPOSS diethyl phosphate group is hydrolyzed into phosphoric hydroxyl groups in an aqueous organic solvent, and then subjected to a dehydration condensation reaction with nano-zirconia in the presence of an acidic catalyst. Through covalent bonding of phosphate ester, phosphate ester modified nano-zirconia loaded with heptavinylPOSS groups is obtained.
[0031] Step 3: Dicumyl peroxide dissolved in white oil is premixed with DOPO functionalized heptavinyl zirconium-containing POSS and phosphate-modified nano-zirconia carrying heptavinyl POSS groups, and then melt-blended with isotactic polypropylene resin in a co-rotating twin-screw extruder, granulated, and dried to obtain high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch.
[0032] Step 4: First, mix polyvinyl alcohol resin and glycerin evenly to obtain plasticized modified polyvinyl alcohol resin. Then, melt-blend and extrude isotactic polypropylene resin, maleic anhydride-grafted polypropylene resin and plasticized modified polyvinyl alcohol resin through a co-rotating twin-screw extruder, granulate, and dry to obtain lyophilic polypropylene masterbatch.
[0033] Step 5: According to the battery separator formula, a battery separator with a thickness of 18-25μm is prepared by a three-layer co-extrusion blown film process and a progressive biaxial stretching process.
[0034] Preferably, the process parameters for the three-layer co-extrusion blown film process are as follows:
[0035] The surface layer corresponds to three temperature zones for the screw extruder: 145-155℃, 160-170℃, and 180-190℃.
[0036] The screw extruder temperature corresponding to the intermediate layer is set in three zones: 155-165℃, 170-180℃, and 185-195℃.
[0037] The die head temperature is 175-185℃, and the blow-up ratio is 2.5-2.9;
[0038] Preferably, the process parameters for the step-by-step biaxial stretching process are as follows:
[0039] First, perform cold stretching at 25-40℃, with a stretching rate of 15-25mm / min and a transverse / longitudinal stretching ratio of 1.2-1.8 times.
[0040] Then perform hot stretching at 120-130℃, with a preheating time of 10-20s, a stretching rate of 5-15mm / min, and a transverse / longitudinal stretching ratio of 1.5-2.5 times.
[0041] Finally, heat setting is performed at a temperature of 125-135℃ for 2-5 minutes.
[0042] Preferably, the preparation method of the diethyl phosphate functionalized heptavinyl POSS is as follows: using 1 molar equivalent of octavinyl-POSS and 0.95-0.98 molar equivalent of diethyl phosphite as raw materials, azobisisobutyronitrile as initiator, a single pH addition reaction is carried out in anhydrous toluene under nitrogen protection to obtain diethyl phosphate functionalized heptavinyl POSS.
[0043] Preferably, the method for preparing the DOPO-functionalized heptvinylzirconium-containing POSS is as follows:
[0044] First, under the action of tetraethylammonium hydroxide, the Si-O-Si bond at one vertex of octavinyl-POSS is opened to generate an incompletely condensed POSS containing three silanol groups. Then, the three silanol groups undergo a condensation reaction with tetrabutyl zirconate. The three butoxy groups of tetrabutyl zirconate react with Si-OH to form Si-O-Zr bonds, capping the opened vertex and producing a monobutoxy heptavinyl zirconium-containing POSS.
[0045] Using 1 molar equivalent of vinyldimethylethoxysilane and 1 molar equivalent of DOPO as raw materials, and azobisisobutyronitrile as initiator, a pH addition reaction was carried out in anhydrous chloroform under nitrogen protection to obtain DOPO-based dimethylethoxysilane.
[0046] Using 1 molar equivalent of monobutoxyheptavinylzirconium-containing POSS and 1 molar equivalent of DOPO-based dimethylethoxysilane as raw materials, the ethoxysilyl group of DOPO-based dimethylethoxysilane was hydrolyzed into silanol groups in an aqueous organic solvent. Under anhydrous toluene reflux conditions, the silanol groups underwent a direct de-alcohol condensation reaction with the butoxy group of monobutoxyheptavinylzirconium-containing POSS to generate Si-O-Zr covalent bonds and release butanol byproducts, thus obtaining DOPO-functionalized heptavinylzirconium-containing POSS.
[0047] This invention utilizes a bulk modification strategy to directly introduce functionalized modified components into a polypropylene resin matrix, resulting in the following significant beneficial effects:
[0048] (1) Solve the problems of interface delamination and pore blockage to improve battery energy density:
[0049] This invention abandons the traditional surface coating process. By preparing hydrophilic polypropylene masterbatch and high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch, functional components are uniformly dispersed inside the membrane matrix. This fundamentally avoids the delamination problem caused by insufficient interfacial bonding between the coating and the matrix. Furthermore, the functional components do not occupy the pores on the membrane surface, effectively preventing the problems of decreased ionic conductivity and reduced energy density caused by excessive coating thickness.
[0050] (2) Significantly improves electrolyte wettability and reduces interfacial impedance:
[0051] This invention involves plasticizing polyvinyl alcohol resin and then using a compatibilizer to composite modify polypropylene, successfully introducing polar hydrophilic groups. This improves the non-polar characteristics of the polypropylene membrane surface, increases the membrane's affinity for the electrolyte (contact angle as low as 28.3°), thereby effectively reducing the battery's interfacial impedance and increasing ionic conductivity (up to 3.0 mS / cm).
[0052] (3) Improve heat resistance and dimensional stability:
[0053] By utilizing the chemical bonding between phosphate-modified nano-zirconia with heptavinyl POSS groups and DOPO-functionalized heptavinyl zirconium-containing POSS and polypropylene resin, a rigid heat-resistant framework was constructed. The unique cage-like siloxane structure of POSS and the high heat resistance of nano-zirconia synergistically improved the heat distortion temperature of the separator, effectively inhibited the thermal shrinkage of polypropylene at high temperature (longitudinal thermal shrinkage rate <4% at 130℃ / 1h), prevented short circuits inside the battery due to separator shrinkage, and greatly improved the high-temperature safety of the battery.
[0054] (4) Phosphorus-silicon-zirconium synergistic flame retardancy:
[0055] This invention constructs a phosphorus-silicon-zirconium multi-element synergistic flame retardant system in the separator matrix. This system can promote the formation of a dense and stable ceramicized carbon layer during combustion (silicon-zirconium synergy) and release phosphorus-containing free radicals to capture combustion chain free radicals (gas-phase flame retardancy), thereby effectively inhibiting the combustion spread of the polyolefin matrix (achieving V-0 flame retardancy). Compared with conventional additive flame retardants, the bonded flame retardant structure of this invention avoids the precipitation and migration of flame retardants, endows the separator with long-lasting flame retardant self-extinguishing ability, and significantly reduces the risk of battery fire and explosion.
[0056] (5) Excellent mechanical properties:
[0057] By chemically bonding inorganic nanoparticles with the polymer matrix, the problems of inorganic particle agglomeration and interfacial stress concentration are solved. The nano-zirconia and POSS rigid particles are uniformly dispersed in the matrix, which act as physical cross-linking points and reinforcing fillers, significantly improving the tensile strength (102-110MPa) and puncture resistance (0.35-0.45N / μm) of the membrane, and effectively resisting lithium dendrite puncture.
[0058] The molecular design logic and mechanism of action of the above-mentioned technical solution of the present invention are as follows:
[0059] By integrating vinyl-POSS and diethyl phosphite groups into a single molecule, the surface of nano-zirconia was modified, thereby introducing reactive sites and flame-retardant functionalization on the surface of zirconia. This solved the problem of nanoscale dispersion of zirconia in a polypropylene matrix and produced phosphate-modified nano-zirconia loaded with heptavinylPOSS groups.
[0060] Furthermore, using vinyl-POSS as the basic structural unit, zirconium was introduced and DOPO groups were grafted to synthesize DOPO-functionalized heptvinyl zirconium-containing POSS;
[0061] Using dicumyl peroxide as a free radical initiator, the free radicals generated by the thermal decomposition of DCP extract hydrogen atoms from the PP main chain to generate macromolecular free radicals, which then undergo free radical addition reactions with the vinyl double bonds in DOPO-functionalized heptavinyl zirconium-containing POSS and phosphate ester-modified nano-zirconia carrying heptavinyl POSS groups to form C-C covalent bonds. This ensures the uniform dispersion and anchoring of the functional modified components in the PP matrix, avoiding the aggregation of nanoparticles and the migration and precipitation of flame retardant components. Detailed Implementation
[0062] The main raw materials used in this invention are as follows:
[0063] Isotactic polypropylene resin (PP), model F401;
[0064] Maleic anhydride-grafted polypropylene resin (PP-g-MAH), model QB510;
[0065] Polyvinyl alcohol resin (PVA), model number 28-98;
[0066] Calcium pimecrolate nucleating agent, CAS number 19455-79-9;
[0067] Antioxidant 1010, CAS number 6683-19-8;
[0068] Octadecyl-POSS, CAS No. 69655-76-1;
[0069] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), CAS No. 35948-25-5;
[0070] Diethyl phosphite, CAS number 762-04-9;
[0071] Tetrabutyl zirconate, CAS number 1071-76-7;
[0072] Vinyl dimethyl ethoxysilane, CAS number 5356-83-2;
[0073] Nano-zirconia with a particle size of 20-30 nm;
[0074] Example 1:
[0075] A battery separator I, the product structure of which consists of the following layers arranged sequentially:
[0076] Surface layer: The formula consists of 40wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 57wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0077] Intermediate layer: The formula consists of 40wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent and 58wt% high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch, with a dosage of 50 parts by weight.
[0078] Surface layer: The formula consists of 40wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 57wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0079] The formulation of the hydrophilic polypropylene masterbatch is as follows: 100 parts by weight of isotactic polypropylene resin, 40 parts by weight of polyvinyl alcohol resin, 10 parts by weight of maleic anhydride grafted polypropylene resin (compatibility agent) and 5 parts by weight of glycerol (plasticizer).
[0080] The formulation of high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch is as follows: 100 parts by weight of isotactic polypropylene resin, 5 parts by weight of nano-zirconia, 0.5 parts by weight of diethyl phosphate functionalized heptavinyl POSS, 2 parts by weight of DOPO functionalized heptavinyl zirconium-containing POSS, 0.2 parts by weight of dicumyl peroxide (free radical initiator), and 0.5 parts by weight of white oil (for dissolving the initiator).
[0081] The preparation method of diethyl phosphate functionalized heptavinyl POSS is as follows: using 1 molar equivalent of octavinyl-POSS and 0.98 molar equivalent of diethyl phosphite as raw materials, and azobisisobutyronitrile (AIBN) as initiator (1 mol%, based on the reaction sites of diethyl phosphite), a single pH addition reaction is carried out in anhydrous toluene under nitrogen protection to obtain diethyl phosphate functionalized heptavinyl POSS, whose chemical structural formula is:
[0082] ;
[0083] The preparation steps of diethyl phosphate functionalized heptavinyl POSS are as follows: Under nitrogen protection, 6.3 g of octavinyl-POSS and 1.3 g of diethyl phosphite were added to a dry 250 mL round-bottom flask, and 70 mL of anhydrous toluene was added. The mixture was stirred at room temperature for 30 min. Then, 0.016 g of AIBN was dissolved in 1 mL of anhydrous toluene to form an AIBN solution. The solution was added to the flask in three batches at 20 min intervals using a constant pressure funnel. The mixture was heated to 70 °C and stirred for 10 h. After cooling to room temperature, the upper layer of toluene was poured off. The lower crude product was first dissolved in 100 mL of dichloromethane, and then precipitated with ethyl acetate at a ratio of 1:10. The product was then filtered under vacuum and dried to obtain diethyl phosphate functionalized heptavinyl POSS.
[0084] The proton NMR spectrum of diethyl phosphate functionalized heptavinyl POSS is as follows: 1H NMR (CDCl3, 400MHz) δ: 0.94-0.96 (t, 2H), 1.35-1.38 (t, 6H), 2.09-2.15 (m, 2H), 4.17-4.23 (m, 4H), 5.36-5.43 (m, 7H), 5.71-5.83 (m, 14H);
[0085] The preparation method of DOPO-functionalized heptvinyl zirconium-containing POSS is as follows:
[0086] First, octavinyl-POSS, under the action of tetraethylammonium hydroxide, opens the Si-O-Si bond at one vertex, generating an incompletely condensed POSS containing three silanol groups. Then, the three silanol groups undergo a condensation reaction with tetrabutyl zirconate. The three butoxy groups of tetrabutyl zirconate react with Si-OH to form Si-O-Zr bonds, capping the opened vertex. The monobutoxyheptavinyl zirconium-containing POSS has the following chemical structure:
[0087] ;
[0088] Using 1 molar equivalent of vinyldimethylethoxysilane and 1 molar equivalent of DOPO as raw materials, and azobisisobutyronitrile (AIBN) as initiator (1 mol%, based on the DOPO reaction sites), a pH addition reaction was carried out in anhydrous chloroform under nitrogen protection to yield DOPO-based dimethylethoxysilane, whose chemical structural formula is as follows:
[0089] ;
[0090] Using 1 molar equivalent of monobutoxyheptavinylzirconium-containing POSS and 1 molar equivalent of DOPO-based dimethylethoxysilane as raw materials, the ethoxysilyl group of DOPO-based dimethylethoxysilane was hydrolyzed to a silanol group in an aqueous organic solvent. Under anhydrous toluene reflux conditions, the silanol group underwent a direct de-alcohol condensation reaction with the butoxy group of monobutoxyheptavinylzirconium-containing POSS to generate a Si-O-Zr covalent bond and release butanol as a byproduct, yielding DOPO-functionalized heptavinylzirconium-containing POSS with the following chemical structural formula:
[0091] ;
[0092] The specific experimental steps for preparing DOPO-functionalized heptvinyl zirconium-containing POSS are as follows:
[0093] Under nitrogen protection, 8.0 g of octavinyl-POSS was added to a dry 250 mL round-bottom flask, followed by 70 mL of anhydrous tetrahydrofuran. The mixture was stirred at room temperature until completely dissolved. Then, 10 mL of 30 wt% tetraethylammonium hydroxide aqueous solution was added to a three-necked flask, and the mixture was heated to 70 °C and refluxed with stirring for 5 h. After cooling to room temperature, the pH was adjusted to neutral using 0.1 mol / L dilute hydrochloric acid. The solvent was removed by rotary evaporation under reduced pressure. The crude product was dissolved in 50 mL of anhydrous diethyl ether, dried with anhydrous sodium sulfate for 2 h, filtered to remove the desiccant, and the diethyl ether was removed by rotary evaporation. After drying, 5.8 g of the product was collected. The substance was added to a dry 250 mL round-bottom flask. Under nitrogen protection, 50 mL of anhydrous tetrahydrofuran was injected and stirred at room temperature until completely dissolved. Then, the flask was placed in an ice-water bath. 20 mL of anhydrous tetrahydrofuran solution containing 4.0 g of tetrabutyl zirconate was added dropwise to the three-necked flask. The mixture was stirred in the ice-water bath for 30 min, then the ice-water bath was removed, and the mixture was stirred at room temperature for 12 h. The tetrahydrofuran and butanol produced in the reaction were removed by rotary evaporation under reduced pressure. The crude product was dissolved in 40 mL of anhydrous acetonitrile, filtered, and the filter cake was washed with anhydrous acetonitrile. After drying, monobutoxyheptavinyl zirconium-containing POSS was obtained.
[0094] Under nitrogen protection, 2.2 g DOPO and 1.3 g vinyldimethylethoxysilane were added to a dry 100 mL round-bottom flask, and 30 mL anhydrous chloroform was added. The mixture was stirred at room temperature for 30 min, and then heated to 50 °C and stirred until completely dissolved. Then, 0.016 g AIBN was dissolved in 1 mL anhydrous chloroform to form an AIBN solution at 50 °C. The solution was added to the flask in three batches at 20 min intervals using a constant pressure funnel. After the addition was complete, the temperature was raised to 65 °C and the mixture was stirred and refluxed for 10 h. The mixture was cooled to room temperature, and the solvent was removed by rotary evaporation. After drying, DOPO-based dimethylethoxysilane was obtained.
[0095] 2.5 g of DOPO-based dimethylethoxysilane was dissolved in 30 mL of anhydrous methanol. 2 mL of deionized water and 0.2 mL of glacial acetic acid were added as catalysts. The mixture was stirred at room temperature for 4 h to hydrolyze the ethoxysilyl group to silanol. The solvent was removed by rotary evaporation under reduced pressure. The crude product was dissolved in 30 mL of anhydrous diethyl ether, dried with anhydrous sodium sulfate for 2 h, filtered to remove the desiccant, and the diethyl ether was removed by rotary evaporation. After drying, 1.6 g of the product and 3.7 g of monobutoxyheptavinyl zirconium-containing POSS were added to a dry 100 mL round-bottom flask. 50 mL of anhydrous toluene was added, and the mixture was stirred and mixed at room temperature for 30 min. Under nitrogen protection, the mixture was heated to 115 °C and refluxed for 6 h. After cooling to room temperature, the solvent was removed by rotary evaporation under reduced pressure. After drying, DOPO-functionalized heptavinyl zirconium-containing POSS was obtained.
[0096] The 1H NMR characterization of DOPO-functionalized heptavinyl zirconium-containing POSS is as follows: 1H NMR (CDCl3, 400MHz) δ: 0.22 (s, 6H), 1.41-1.43 (t, 2H), 2.43-2.48 (m, 2H), 5.23-5.32 (m, 7H), 5.71-5.85 (m, 14H), 7.26-8.13 (m, 8H).
[0097] Example 2:
[0098] A process for preparing a battery separator I includes the following steps:
[0099] Step 1: Preparation of hydrophilic polypropylene masterbatch:
[0100] The polyvinyl alcohol resin was dried in a vacuum oven at 80°C for 10 hours until the moisture content dropped to below 0.1%, and then set aside for later use.
[0101] 40 parts by weight of dried polyvinyl alcohol resin were added to a high-speed mixer. The polyvinyl alcohol resin was heated to 75°C by stirring and friction at 1800 rpm. Then, 5 parts by weight of glycerol were added in 3 batches at 5-minute intervals while maintaining the speed of 1800 rpm. The mixture was stirred and mixed for 10 minutes to obtain plasticized modified polyvinyl alcohol resin.
[0102] 100 parts by weight of isotactic polypropylene resin, 10 parts by weight of maleic anhydride-grafted polypropylene resin and 45 parts by weight of plasticized modified polyvinyl alcohol resin were fed into a co-rotating twin-screw extruder for melt blending and extrusion. After the extruded material was cooled in a water tank, it was granulated by a pelletizer and then vacuum dried at 60°C for 4 hours to obtain a hydrophilic polypropylene masterbatch.
[0103] The temperature settings for each zone of the twin-screw extruder are as follows: Zone 1 160℃, Zone 2 165℃, Zone 3 170℃, Zone 4 175℃, Zone 5 180℃, Zone 6 185℃, Zone 7 (distillation head) 185℃; Preheating temperature 160℃; Screw speed 120r / min.
[0104] Step two involves preparing high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch, including the following processes:
[0105] (1) Preparation of phosphate-modified nano-zirconia loaded with heptavinylPOSS groups: The diethyl phosphate group of heptavinylPOSS functionalized by diethyl phosphate is hydrolyzed into phosphoric hydroxyl groups in an aqueous organic solvent and then subjected to dehydration condensation reaction with nano-zirconia (containing hydroxyl functional groups on the surface) dispersed in an anhydrous organic solvent in the presence of an acidic catalyst. Through covalent bonding of phosphate ester, phosphate-modified nano-zirconia loaded with heptavinylPOSS groups is obtained.
[0106] The preparation steps are as follows: 0.5 parts by weight of diethyl phosphate functionalized heptavinyl POSS was dispersed in 30 parts by weight of anhydrous methanol, 5 parts by weight of deionized water and 0.5 parts by weight of concentrated hydrochloric acid were added for catalysis, and the mixture was stirred at room temperature for 5 h to hydrolyze the diethyl phosphate group into phosphoric hydroxyl groups; 5 parts by weight of nano-zirconia was ultrasonically dispersed in 100 parts by weight of anhydrous methanol, and then the hydrolysate was slowly added to the nano-zirconia dispersion. The mixture was heated to 60℃ and stirred for 12 h, cooled to room temperature, and separated by centrifugation (8000 rpm, 15 min). The nano-zirconia was washed twice with methanol, once with deionized water, and once with methanol, and dried to obtain phosphate-modified nano-zirconia loaded with heptavinyl POSS groups.
[0107] (2) Preparation of high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch:
[0108] First, 0.2 parts by weight of dicumyl peroxide dissolved in 0.5 parts by weight of white oil, 2 parts by weight of DOPO-functionalized heptavinyl zirconium-containing POSS, and 5.5 parts by weight of phosphate-modified nano-zirconia with heptavinyl POSS groups were premixed evenly at room temperature. Then, it was thoroughly mixed with 100 parts by weight of isotactic polypropylene resin and fed into a co-rotating twin-screw extruder for melt blending reaction extrusion. After the extruded material was cooled in a water tank, it was granulated by a pelletizer and then vacuum dried at 60°C for 4 hours to obtain high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch.
[0109] The temperature settings for each zone of the twin-screw extruder are as follows: Zone 1 170℃, Zone 2 175℃, Zone 3 180℃, Zone 4 185℃, Zone 5 190℃, Zone 6 195℃, Zone 7 (distillation head) 195℃; Preheating temperature 170℃; Screw speed 150r / min.
[0110] Step 3, preparation of high-performance polypropylene composite film I: The raw materials of each film layer are respectively fed into the hoppers of the three screw extruders of the three-layer co-extrusion film blow molding unit. The molten resin is combined at the die head through the distributor, extruded and blown by the die head, cooled and wound up to obtain high-performance polypropylene composite film I.
[0111] The process parameters for the three-layer co-extrusion film blow molding unit are as follows:
[0112] The surface layer corresponds to a screw extruder temperature zone with three settings: 150℃, 165℃, and 185℃, and a screw speed of 40 r / min.
[0113] The screw extruder temperature corresponding to the intermediate layer is set in three zones: 160℃, 175℃, and 190℃, and the screw speed is 60r / min.
[0114] Die head temperature 180℃; blow-up ratio 2.9; traction speed 5.0m / min; cooling air temperature 20℃;
[0115] Step 4, Preparation of battery separator I: The high-performance polypropylene composite membrane I prepared in step 3 was annealed in a 125℃ oven for 3 hours, and then fixed on the fixture of a biaxial tensile testing machine. A step-by-step biaxial tensile process was adopted. First, cold stretching was performed at 30℃ with a stretching rate of 20 mm / min and a stretching ratio of 1.5 (transverse) × 1.5 (longitudinal). Then, hot stretching was performed at 125℃ with a preheating time of 15 s, a stretching rate of 10 mm / min, and a stretching ratio of 2.0 (transverse) × 2.0 (longitudinal). Finally, heat setting was performed at a setting temperature of 130℃ for 3 minutes to obtain a battery separator I with a thickness of 20 μm.
[0116] Example 3:
[0117] A battery separator II, the product structure of which consists of the following layers arranged sequentially:
[0118] Surface layer: The formulation consists of 60wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 37wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0119] Intermediate layer: The formula consists of 60wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent and 38wt% high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch, with a dosage of 50 parts by weight.
[0120] Surface layer: The formulation consists of 60wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 37wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0121] The preparation process of battery separator II is the same as that of battery separator I in Example 2, resulting in battery separator II with a thickness of 20 μm.
[0122] Example 4:
[0123] A battery separator III has the following layers arranged sequentially:
[0124] Surface layer: The formulation consists of 80wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 17wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0125] Intermediate layer: The formula consists of 80wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent and 38wt% high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch, with a dosage of 18 parts by weight.
[0126] Surface layer: The formulation consists of 80wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 17wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0127] The preparation process of battery separator III is the same as that of battery separator I in Example 2, resulting in battery separator III with a thickness of 20 μm.
[0128] Comparative Example 1:
[0129] A battery separator a has the following product structure consisting of the following layers arranged sequentially:
[0130] Surface layer: The formulation consists of 60wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 37wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0131] Intermediate layer: The formulation consists of 60wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent and 38wt% polypropylene-zirconia blend masterbatch, with a dosage of 50 parts by weight.
[0132] Surface layer: The formulation consists of 60wt% isotactic polypropylene resin, 2wt% calcium pimecronate nucleating agent, 1wt% antioxidant 1010 and 37wt% hydrophilic polypropylene masterbatch, with a dosage of 25 parts by weight.
[0133] The preparation process of a battery separator a is the same as that of battery separator I in Example 2, and a battery separator a with a thickness of 20 μm is obtained.
[0134] The formula for the polypropylene-zirconia blend masterbatch is: 100 parts by weight of isotactic polypropylene resin and 7 parts by weight of nano-zirconia.
[0135] The preparation method of polypropylene-zirconia blend masterbatch is as follows: 7 parts by weight of nano-zirconia and 100 parts by weight of isotactic polypropylene resin are fully mixed and then fed into a co-rotating twin-screw extruder through a hopper for melt physical blending extrusion; after the extruded material is cooled by a water tank, it is granulated by a pelletizer and then vacuum dried at 60°C for 4 hours to obtain polypropylene-zirconia blend masterbatch.
[0136] The temperature settings for each zone of the twin-screw extruder are as follows: Zone 1 170℃, Zone 2 175℃, Zone 3 180℃, Zone 4 185℃, Zone 5 190℃, Zone 6 195℃, Zone 7 (distillation head) 195℃; preheating temperature 170℃; screw speed 150r / min.
[0137] Comparative Example 2:
[0138] A battery separator b, the product structure of which consists of the following layers arranged sequentially:
[0139] Surface layer: The formula consists of 97 wt% isotactic polypropylene resin, 2 wt% calcium pimecronate nucleating agent and 1 wt% antioxidant 1010, with a dosage of 25 parts by weight.
[0140] Intermediate layer: The formulation consists of 98wt% isotactic polypropylene resin and 2wt% calcium pimecronate nucleating agent, with a dosage of 50 parts by weight.
[0141] Surface layer: The formula consists of 97 wt% isotactic polypropylene resin, 2 wt% calcium pimecronate nucleating agent and 1 wt% antioxidant 1010, with a dosage of 25 parts by weight.
[0142] The preparation process of a battery separator b is the same as that of battery separator I in Example 2, resulting in a battery separator b with a thickness of 20 μm.
[0143] Performance testing:
[0144] I. Porosity Test: The porosity of the membrane sample was tested using the liquid absorption and weighing method. The specific test steps were as follows: A 2cm × 2cm membrane sample was dried to constant weight and recorded as m0g. Then, it was immersed in n-butanol at room temperature (25℃) for 4 hours. After removal, the membrane sample was sandwiched between two pieces of dry filter paper and pressure was applied using a 20g weight for 10 seconds to absorb excess n-butanol from the surface. The weight was recorded as m1g. The porosity of the membrane sample was calculated using the following method:
[0145] Porosity (%) = (m1 - m0) / (ρ) 正丁醇 ×V 膜 )×100%;
[0146] Where, ρ 正丁醇 The density of n-butanol is ρ at 25°C. 正丁醇 =0.81g / mL; V 膜 This represents the volume of the diaphragm sample.
[0147] II. Hydrophilicity Test: The electrolyte contact angle of the diaphragm sample was tested using a contact angle meter. The specific test steps were as follows: The sample was placed stably on the stage of the contact angle meter. A 4μL electrolyte droplet (1mol / L lithium hexafluorophosphate dissolved in a 1:1 mixture of diethyl carbonate and ethylene carbonate, with 10vol% fluoroethylene carbonate added) was injected onto the sample surface using a microsyringe (the test environment temperature was controlled at 25℃ and the relative humidity was maintained at 50%). When the droplet was stable, the contact angle of the sample surface was measured.
[0148] III. Mechanical property testing:
[0149] (1) Tensile strength test: In accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets", the tensile strength of the diaphragm sample was tested using a universal tensile testing machine. The specific test steps were as follows: a 130mm×15mm (length×width, with the length direction being the blow molding direction (longitudinal)) sample was fixed on the tensile testing machine and a tensile test was performed along the blow molding direction at a tensile rate of 250mm / min. The longitudinal tensile strength of the sample was recorded and calculated.
[0150] (2) Puncture resistance test: According to GB / T 37841-2019 "Test method for puncture resistance of plastic films and sheets", a 5cm×5cm film sample was fixed on the puncture resistance tester. The puncture needle was made of stainless steel with a diameter of 1.0mm and a hemispherical tip with a radius of 0.5mm. The puncture rate was 100mm / min. The puncture resistance of the sample was recorded.
[0151] IV. Heat Resistance Test: The heat shrinkage rate of the diaphragm sample was tested according to GB / T 12027-2004 "Test Method for Dimensional Change Rate of Plastic Films and Sheets under Heating". The specific test steps are as follows: A 120mm×120mm sample (length×width, with the length direction being the blow molding direction (longitudinal), and the initial longitudinal length L0 marked in the middle of the sample) was placed in an environment of 130℃ for 1 hour, then removed and placed in an environment of room temperature (25℃) for 30 minutes. The length between the marks L1 after heating was measured again, and the longitudinal heat shrinkage rate of the diaphragm sample (130℃ / 1h) was calculated. The specific calculation method is as follows:
[0152] Longitudinal thermal shrinkage rate (%) = (L0 - L1) / L0 × 100%;
[0153] V. Flame retardant performance test (UL-94 test): According to GB / T 2408-2021 "Determination of flammability of plastics - Horizontal and Vertical Methods", 125mm×13mm samples (length×width) are stacked in the same direction to a thickness of 3mm, with natural adhesion between layers, without the use of adhesives, and the test is conducted using test method B - Vertical Flammability Test.
[0154] VI. Electrochemical Performance Testing: The ionic conductivity of the membrane sample was tested using an electrochemical workstation via AC impedance spectroscopy. The specific testing steps were as follows: The sample was cut into small circular pieces with a diameter of 18 mm. In an argon-filled glove box, the stainless steel electrode sheet, the circular membrane sample, the stainless steel electrode sheet, and the spring were placed sequentially into a stainless steel battery casing. 50 μL of electrolyte (1 mol / L lithium hexafluorophosphate dissolved in a 1:1 volume ratio of diethyl carbonate and ethylene carbonate mixed solvent, with 10 vol% fluoroethylene carbonate added) was added. The casing was then sealed and allowed to stand for 24 h. The electrochemical workstation was used to test the impedance spectrum at an AC amplitude of 5 mV, a frequency range of 1 MHz-1 Hz, and an equilibrium time of 2 s. The bulk resistance of the membrane sample was recorded, and the ionic conductivity was calculated. The specific calculation method is as follows:
[0155] Ionic conductivity (mS / cm) = d / (R×A);
[0156] Where d is the film thickness, R is the bulk resistance, and A is the area of the stainless steel electrode sheet;
[0157] The results of the above performance experiments are shown in Table 1.
[0158] Table 1. Experimental results of battery separator performance
[0159]
[0160] The following conclusions can be drawn from the experimental results:
[0161] Conclusion 1: Lyophilic polypropylene masterbatch has an enhancing effect on the lyophilic properties of membranes.
[0162] The contact angles of diaphragms I-III in Examples and diaphragm a in Comparative Example were all <35°, significantly lower than that of diaphragm b in Comparative Example (70.8°) which did not contain hydrophilic polypropylene masterbatch. This is attributed to the fact that the hydroxyl groups on the PVA molecular chains in the hydrophilic polypropylene masterbatch form strong hydrogen bonds and dipole-dipole interactions with the polar parts such as carbonyl groups or ether oxygen bonds in the electrolyte solvent molecules, thereby overcoming the surface tension of the liquid. This allows the electrolyte to spread rapidly on the diaphragm surface and penetrate into the internal pores. The higher the amount of hydrophilic polypropylene masterbatch added (diaphragm III > diaphragm I > diaphragm II), the better the hydrophilic performance.
[0163] The ionic conductivity of the membranes in Examples I-III was increased by 90-130% compared to that of the comparative example membrane b, which also proves the above conclusion, because the hydrophilic properties of the membrane have a significant impact on its ionic conductivity.
[0164] Conclusion 2: The effect of high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch on the mechanical and heat resistance properties of the diaphragm:
[0165] The longitudinal tensile strength of diaphragm II in Example II is 107.9 MPa, the puncture resistance is 0.40 N / μm, and the longitudinal heat shrinkage rate is 2.6%. Compared with diaphragm a (88.5 / 0.14 / 10.6) using zirconium dioxide blend, it has achieved significant improvements in mechanical properties and heat resistance.
[0166] The introduction of nano-zirconia can enhance the heat resistance of the membrane to a certain extent. However, the introduction of nano-zirconia through physical blending will destroy the continuity and crystalline structure of the polymer matrix. Furthermore, the poor interfacial compatibility between inorganic zirconia and organic polypropylene matrix leads to a decrease in the overall mechanical properties of the membrane while the improvement in high-temperature resistance is limited.
[0167] By covalently bonding nano-zirconia modified with diethyl phosphate-functionalized heptavinyl POSS and DOPO-functionalized heptavinyl zirconium-containing POSS to the polypropylene matrix, not only is the interfacial bonding good, achieving nano-dispersion of fillers at the polypropylene molecular level, but it also fundamentally solves the problem of interfacial stress concentration, ultimately achieving a synergistic improvement in the mechanical properties and heat resistance of the diaphragm.
[0168] Conclusion 3: The diaphragm products prepared by this invention exhibit excellent flame retardant properties, with flame retardant ratings reaching V-0.
[0169] Among them, the phosphorus-silicon-zirconium synergistic flame retardant mechanism plays a core role: when heated, the polyphosphoric acid produced by the degradation of phosphate ester groups acts as an acid source, catalyzing the dehydrogenation crosslinking of the polypropylene matrix and promoting the formation of a char layer; at the same time, the heptavinyl POSS skeleton is transformed into a SiO2-ZrO2 inorganic hybrid network through high-temperature oxidation, and the phosphorus, silicon and zirconium products are combined through PO-Si and Si-O-Zr bonds to form a dense hybrid ceramic layer. This layer is dense and continuous and resistant to thermal erosion. It can not only isolate the transfer of combustible gases, oxygen and heat, but also inhibit the high-temperature melting shrinkage of the polypropylene matrix through the rigid SiO2-ZrO2 network, thus achieving efficient condensed phase flame retardancy and structural stability.
Claims
1. A battery separator, characterized in that, The diaphragm has a surface / intermediate / surface co-extrusion structure; The surface layer is formulated with 40-80 wt% isotactic polypropylene resin, 1-3 wt% nucleating agent, 0.5-2 wt% antioxidant and 17-57 wt% hydrophilic polypropylene masterbatch. The intermediate layer is formulated with 40-80 wt% isotactic polypropylene resin, 1-3 wt% nucleating agent and 17-57 wt% high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch. The hydrophilic polypropylene masterbatch is prepared by compounding plasticized modified polyvinyl alcohol resin with polypropylene resin under the action of a compatibilizer. The high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch is prepared by compounding polypropylene resin with phosphate-modified nano-zirconia and DOPO-functionalized heptavinyl POSS groups via free radical grafting reaction and C-C covalent bonding. The chemical structural formula of the DOPO-functionalized heptavinyl zirconium-containing POSS is as follows: 。 2. The battery separator according to claim 1, characterized in that, The phosphate-modified nano-zirconia loaded with heptavinylPOSS groups was prepared by functionalizing heptavinylPOSS with diethyl phosphate and anchoring it to the surface of nano-zirconia via phosphate covalent bonds. The chemical structural formula of the diethyl phosphate-functionalized heptavinyl POSS is as follows: 。 3. The battery separator according to claim 1, characterized in that, The formulation of the hydrophilic polypropylene masterbatch is as follows: 80-120 parts by weight of isotactic polypropylene resin; 30-50 parts by weight of polyvinyl alcohol resin 5-15 parts by weight of maleic anhydride-grafted polypropylene resin; 3-8 parts by weight of glycerin.
4. A battery separator according to claim 1, characterized in that, The formulation of the high-strength, high-temperature resistant, flame-retardant polypropylene masterbatch is as follows: 80-120 parts by weight of isotactic polypropylene resin; 3-8 parts by weight of nano-zirconia; 0.3-0.8 parts by weight of diethyl phosphate-functionalized heptavinyl POSS; 1-5 parts by weight of DOPO functionalized heptavinyl zirconium-containing POSS; 0.1-0.5 parts by weight of dicumyl peroxide; 0.3-0.8 parts by weight of white oil.
5. A battery separator according to claim 4, characterized in that, The nano-zirconia has a particle size of 20-30 nm.
6. A battery separator according to claim 1, characterized in that, The nucleating agent is calcium pimerate; The antioxidant is antioxidant 1010.
7. The process for preparing a battery separator according to any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Using octavinyl-POSS as the starting material, diethyl phosphate-functionalized heptavinyl-POSS and DOPO-functionalized heptavinyl-zirconium-containing POSS were prepared respectively. Step 2: The diethyl phosphate functionalized heptavinylPOSS diethyl phosphate group is hydrolyzed into phosphoric hydroxyl groups in an aqueous organic solvent, and then subjected to a dehydration condensation reaction with nano-zirconia in the presence of an acidic catalyst. Through covalent bonding of phosphate ester, phosphate ester modified nano-zirconia carrying heptavinylPOSS groups is obtained. Step 3: Dicumyl peroxide dissolved in white oil is premixed with DOPO functionalized heptavinyl zirconium-containing POSS and phosphate-modified nano-zirconia carrying heptavinyl POSS groups, and then melt-blended with isotactic polypropylene resin in a co-rotating twin-screw extruder, granulated, and dried to obtain high-strength, high-temperature resistant, and flame-retardant polypropylene masterbatch. Step 4: First, mix polyvinyl alcohol resin and glycerin evenly to obtain plasticized modified polyvinyl alcohol resin. Then, melt-blend and extrude isotactic polypropylene resin, maleic anhydride-grafted polypropylene resin and plasticized modified polyvinyl alcohol resin through a co-rotating twin-screw extruder, granulate, and dry to obtain lyophilic polypropylene masterbatch. Step 5: According to the battery separator formula, a battery separator with a thickness of 18-25μm is prepared by a three-layer co-extrusion blown film process and a progressive biaxial stretching process.
8. The manufacturing process of a battery separator according to claim 7, characterized in that, The process parameters for the three-layer co-extrusion blown film process are as follows: The surface layer corresponds to three temperature zones for the screw extruder: 145-155℃, 160-170℃, and 180-190℃. The screw extruder temperature corresponding to the intermediate layer is set in three zones: 155-165℃, 170-180℃, and 185-195℃. The die head temperature is 175-185℃, and the blow-up ratio is 2.5-2.9; The process parameters for the step-by-step biaxial stretching process are as follows: First, perform cold stretching at 25-40℃, with a stretching rate of 15-25mm / min and a transverse / longitudinal stretching ratio of 1.2-1.8 times. Then perform hot stretching at 120-130℃, with a preheating time of 10-20s, a stretching rate of 5-15mm / min, and a transverse / longitudinal stretching ratio of 1.5-2.5 times. Finally, heat setting is performed at a temperature of 125-135℃ for 2-5 minutes.
9. The manufacturing process of a battery separator according to claim 7, characterized in that, The preparation method of the diethyl phosphate functionalized heptavinyl POSS is as follows: using 1 molar equivalent of octavinyl-POSS and 0.95-0.98 molar equivalent of diethyl phosphite as raw materials, azobisisobutyronitrile as initiator, a single pH addition reaction is carried out in anhydrous toluene under nitrogen protection to obtain diethyl phosphate functionalized heptavinyl POSS.
10. The manufacturing process of a battery separator according to claim 7, characterized in that, The preparation method of the DOPO-functionalized heptvinyl zirconium-containing POSS is as follows: First, under the action of tetraethylammonium hydroxide, the Si-O-Si bond at one vertex of octavinyl-POSS is opened to generate an incompletely condensed POSS containing three silanol groups. Then, the three silanol groups undergo a condensation reaction with tetrabutyl zirconate. The three butoxy groups of tetrabutyl zirconate react with Si-OH to form Si-O-Zr bonds, capping the opened vertex and producing a monobutoxy heptavinyl zirconium-containing POSS. Using 1 molar equivalent of vinyldimethylethoxysilane and 1 molar equivalent of DOPO as raw materials, and azobisisobutyronitrile as initiator, a pH addition reaction was carried out in anhydrous chloroform under nitrogen protection to obtain DOPO-based dimethylethoxysilane. Using 1 molar equivalent of monobutoxyheptavinylzirconium-containing POSS and 1 molar equivalent of DOPO-based dimethylethoxysilane as raw materials, the ethoxysilyl group of DOPO-based dimethylethoxysilane was hydrolyzed into silanol groups in an aqueous organic solvent. Under anhydrous toluene reflux conditions, the silanol groups underwent a direct de-alcohol condensation reaction with the butoxy group of monobutoxyheptavinylzirconium-containing POSS to generate Si-O-Zr covalent bonds and release butanol byproducts, thus obtaining DOPO-functionalized heptavinylzirconium-containing POSS.